The LRG-TGF-β-Alk-1/TGFßRII-Smads as Predictive Biomarkers of Chronic Hydrocephalus after Aneurysmal Subarachnoid Hemorrhage - Ma, Dongying; Ma, Luyao; Zhao, Yongqiang; Li, Yongli; Ye, Wei; Li, Xianfeng (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Background Chronic hydrocephalus is a common complication of aneurysmal subarachnoid hemorrhage (aSAH); however, the risk factors and the mechanisms underlying its occurrence have yet to be fully elucidated. The purpose of this study was to identify biomarkers that could be used to predict chronic hydrocephalus after aSAH and to investigate the relationships.Methods We analyzed cerebrospinal fluid (CSF) samples from 19 patients with chronic hydrocephalus after aSAH and 44 controls without hydrocephalus after aSAH. Enzyme-linked immunosorbent assay was used to determine the levels of leucine-rich alpha-2-glycoprotein (LRG), transforming growth factor-β (TGF-β), Smad1, Smad4, Smad5, Smad8, activin receptor-like kinase 1 (Alk-1), activin receptor-like kinase 5 (Alk-5), P38, and TGF-β type II receptor (TGFßRII) in CSF samples.Results In the CSF of patients with chronic hydrocephalus after aSAH, the levels of LRG, TGF-β, Alk-1, Smad5, and TGFßRII were significantly increased (p < 0.05) and the levels of Smad1, Smad4, and Smad8 were significantly decreased (p < 0.05). There were no significant differences between the two groups concerning the levels of P38 and Alk-5 (p > 0.05). The analysis also identified significant correlations between specific biomarkers: LRG and Smad1, LRG and Smad5, TGF-β and Alk-1, and Alk-1 and Smad4 (p < 0.05); the Pearson's correlation coefficients for these relationships were −0.341, 0.257, 0.256, and −0.424, respectively.Conclusion The levels of LRG, TGF-β, Alk-1, TGFßRII, Smad1/5/8, and Smad4 in the CSF are potentially helpful as predictive biomarkers of chronic hydrocephalus after aSAH. Moreover, the LRG-TGF-β-Alk-1/TGFßRII-Smad1/5/8-Smad4 signaling pathway is highly likely to be involved in the pathogenic process of chronic hydrocephalus after aSAH.
Keywords: chronic hydrocephalus; subarachnoid hemorrhage; cerebrospinal fluid; leucine-rich alpha-2-glycoprotein; transforming growth factor-β